Self-Efficacy in Disrupted Environments: COVID-19 as a Natural Experiment. (May 2023) - Bergenholtz, Carsten; Klyver, Kim; Vuculescu, Oana
In two studies, we investigate whether the link between entrepreneurial self-efficacy and entrepreneurial intentions depends on outcome expectations. In Study 1, we exploit the COVID-19-induced lockdown as a natural experiment in a two-wave student sample. We compare the efficacy–intention link in survey responses submitted right before and right after the lockdown. In Study 2, we conceptually replicate and extend the findings via an online vignette experiment. Together, these studies show that a disruption of stable institutionalized outcome expectations implying increasing risk and uncertainty makes self-efficacy a weaker predictor of entrepreneurial intentions, particularly among those with pessimistic perceptions.